Raw material depletion and scenario assessment in European Union – A circular economy approach - Martins, Florinda (2022)
Nowadays the production systems are linear and the consumption patterns are essentially based on products with a short life cycle, which contribute to increase the demand for raw materials and environmental impacts. The Circular Economy (CE) is playing a major role among scholars and practitioners. Many aspects are now defining this new trending paradigm such as the roles of product development, transformation and remanufacturing/recycling, and/or management of waste, ensuring the economic and environmental benefits. The increasing demand causes instability of the prices and markets, and there is also the risk of supply rupture. This is very unsustainable and puts at risk countries’ development. In this work we analyze and assess some EU critical raw material (CRM), considering existing global reserves and production. Correlation between several parameters was also analyzed. Under this assumption one scenario was considered to assess the depletion of two CRM. China is the main supplier in 15 out of 25 CRM considered in this analysis and its average percentage is 65%. Phosphate rock presents the highest value and antimony the lowest for depletion indicator. It was possible to conclude that no significant correlation was found between depletion, self-sufficiency and economic importance indicators.